Environmental certification schemes and property values: evidence from the Hong Kong prime commercial office market - Wadu Mesthrige, Jayantha; Chan, Hoi-Ting (International Journal of Strategic Property Management, 2019)
A barrier to green-building development is the uncertainty and scepticism about the financial implications. This study aimed to investigate whether the green-certification schemes help buyers to recognize the benefits of green office buildings by their willingness to pay a premium for such buildings. The study used a hedonic-model based on a sample of 67 prime office buildings (including non-green comparables) certified by HKBEAM, BEAM-Plus and LEED in Hong Kong. The empirical findings suggest that green certification schemes add extra value to an office property. The rental value of office properties certified by HKBEAM, BEAM Plus and LEED is about 10.9% higher than for non-certified office buildings. More specifically, tenants/users are willing to pay a premium of 10.9% for green-certified office properties. The findings have practical implications in encouraging green building development in Hong Kong and elsewhere. The findings indicate that the higher rental income from green office buildings can cover the additional cost of obtaining green certification within a period of 22-months (22.32 months) in Hong Kong. The results provide references for various stakeholders (developers/investors/users) in establishing the business case for green-office buildings, because of the ability of the market to capitalize the environmental benefits of green office properties.